ANALISIS PROTEIN PADA TEPUNG KECAMBAH KACANG HIJAU (Phaseolus aureus L.) YANG DIKECAMBAHKAN MENGGUNAKAN AIR, AIR CUCIAN BERAS DAN AIR KELAPA - dirga dirga (Journal of Science and Applicative Technology, 2018)
Nuts have long been known as a complementary source of protein with whole grains, such as rice and wheat. One of the many types of nuts that are widely available are green beans. Utilization of waste such as coconut water and rice washing water as an additional substance of the plant fertilizer needs to be improved given the high levels of nutrients that can be beneficial to the plant. This study aims to analyze the protein in wheat sprouts green beans (Phaseolus aureus L.) that germinated using the Water, Rice Washing Water and Coconut Water. Wheat sprouts green beans were analyzed qualitatively with the ninhydrin test, test Millon, and biuret test, then quantitatively analyzed by the Kjeldahl method includes the destruction process, distillation and titration. The results showed that Content of protein in wheat sprouts for wheat germination using water 28,50% w/w, protein content in wheat germination using washed rice water 31,19% w/w , and protein content in wheat germination using coconut water 32,06% w/w. The highest protein contained in wheat germ on the germination use coconut water 32,06% w/w.